PENGUKURAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF SISWA SMK TEKNIK PEMESINAN DI KOTA SERANG - Nurlela; Ikhsanudin; Hamid Abdillah (Program Studi Pendidikan Teknologi Informasi Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to determine the level of critical and creative thinking skills of students of Mechanical Engineering Vocational Schools. This study uses a quantitative approach with a survey method and data analysis techniques with descriptive analysis, data collection techniques by distributing essay test sheets to all students of mechanical engineering expertise programs. The results of the study show that: (1). The average level of students' critical thinking skills is low. The low level of critical thinking skills possessed by students is due to the learning process which is less effective in developing the interests, talents and potentials that exist in each student. (2). The average level of students' creative thinking skills is low because many of the answers from students are mostly the same.